A new combination in Erysimum (Brassicaceae) for Baetic mountains (South-eastern Spain) - Lorite, Juan; Perfectti, Francisco; Gómez, Jose María (Phytotaxa, 2015)
According to the new findings on the phylogeny of the genus Erysimum, we propose the new combination Erysimum bastetanum (G. Blanca & C. Morales) Lorite et al. comb. & stat. nov.